Copper-Catalyzed C–S Cross-Coupling Reaction: S-Arylation of Arylthioureas - Zhu, Hui; Liu, Xing; Chang, Cai-Zhu; Dong, Zhi-Bing (Synthesis, 2017)
A simple and efficient copper-catalyzed S-arylation of arylthioureas was developed. Arylthioureas were smoothly converted into aryl-isothioureas with good yield by copper-catalyzed S-arylation. The features of this method include the use of a ligand-free catalyst, good yield, short reaction time, and broad substrate scope. The method provides a facile and convenient preparation of some potentially biologically active compounds.
Keywords: copper; S-arylation; catalysis; thiourea; isothiourea